Temperature dependence of the interfacial magnetic anisotropy in W/CoFeB/MgO - Lee, Kyoung-Min; Choi, Jun Woo; Sok, Junghyun; Min, Byoung-Chul (AMER INST PHYSICS, 2017)
The interfacial perpendicular magnetic anisotropy in W/CoFeB ( 1.2 similar to 3 nm)/MgO thin film structures is strongly dependent on temperature, and is significantly reduced at high temperature. The interfacial magnetic anisotropy is generally proportional to the third power of magnetization, but an additional factor due to thermal expansion is required to explain the temperature dependence of the magnetic anisotropy of ultrathin CoFeB films. The reduction of the magnetic anisotropy is more prominent for the thinner films; as the temperature increases from 300 K to 400 K, the anisotropy is reduced similar to 50% for the 1.2-nm-thick CoFeB, whereas the anisotropy is reduced similar to 30% for the 1.7-nm-thick CoFeB. Such a substantial reduction of magnetic anisotropy at high temperature is problematic for data retention when incorporating W/CoFeB/MgO thin film structures into magneto-resistive random access memory devices. Alternative magnetic materials and structures are required to maintain large magnetic anisotropy at elevated temperatures. (C) 2017 Author(s).